Severe asthma in children - Bush, Andrew (Henry Stewart Talks, 2018)
Examples of representative airway diseases in children, Updating our view about severe asthma, Review of novel mechanistic data in true severe therapy-resistant asthma, Different phenotypes of ‘steroid resistant asthma’ and their management
Archived at 2022/09/29